The Sweet Consumption Trap: The Role Of Brand Image And Sensory Appeal In Sustaining High-Sugar Beverage Consumption - Achmad Ridha; Fina Ruzika Zaimar (International Journal of Education Management and Religion, 2026)
Despite increasing awareness of the health risks associated with excessive sugar consumption, the demand for high-sugar beverages remains persistently high. This phenomenon suggests that factors beyond rational health considerations play a critical role in shaping sustained consumption behavior. This study aims to examine the roles of brand image and sensory appeal in sustaining high-sugar beverage consumption, with emotional attachment serving as a mediating mechanism and health risk awareness included as a control variable. Using a quantitative approach, data were collected through a survey of high-sugar beverage consumers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that both brand image and sensory appeal have significant positive effects on emotional attachment and continuance purchase intention. Emotional attachment emerges as a key predictor of continuance purchase intention and partially mediates the relationships between brand image, sensory appeal, and sustained consumption behavior. Health risk awareness is found to negatively influence continuance purchase intention, although its effect is weaker compared to affective and sensory-driven factors. These findings highlight the presence of a sweet consumption trap, in which emotional and sensory mechanisms reinforce continued consumption despite consumers’ awareness of health risks. The study contributes to the literature by offering an integrated framework that explains the persistence of unhealthy consumption and provides insights for both marketing strategy and public health interventions.